Die aard van wet in die Pentateug: ’n Krities-kanoniese perspektief met Nuwe-Testamentiese implikasie - De Koning, Jacobus de Wit (Stellenbosch Theological Journal, 2017)
The nature of law in the Pentateuch: A critical-canonical perspective with New Testament implication In this study, the question is asked whether the nature of law in the Pentateuch corresponds with the view of the nature of the law as expressed by the Westminster Confession of Faith. The article also explores whether Calvin’s view of the law, as sometimes emerged in his discussion of the guideline for the Christian’s life of gratitude, may not be more in line with it, especially when he sees Christ and the law as interchangeable when it comes to a guideline for Christian life. In the search for an answer to this question, the article looks at researchers’ critical investigation into the authority that legal material in the Pentateuch actually had in the practice of Israel and Judah, in conjunction with a canonical investigation into the nature of the legal material in the Pentateuch. After indication of an implication of this findings for the New Testament Christian, the article comes to the conclusion that Calvin was indeed at times closer to the nature of law in the Pentateuch than the Westminster Confession of Faith.